Inter-religious Studies in Indonesia With Reference to ICRS - Robert Setio (Asosiasi Ahli Filsafat Keilahian Indonesia, 2020)
This article discusses how inter-religious studies is conducted in Indonesia. A case in point is Indonesian Consortium for Religious Studies (ICRS). As one of the founders, Duta Wacana Christian University (UKDW), has its own contributions for ICRS. The Faculty of Theology that plays the actual role as UKDW’s representation in ICRS has made ICRS a continuation of its existence as theological education. In this article, I will describe the link between theology and inter-religious studies as far as the Faculty of Theology UKDW is concerned. Rather than hindering the progress of inter-religious studies as some might worry, theology is in fact can be a significant part of inter-religious studies.